Green microbial self-repairing concrete and preparation method thereof
By using carrier materials in concrete to solid-load nitrate reducing bacteria and modified mesoporous silicon, a three-dimensional network structure is formed, which solves the problem of low efficiency in high alkali environment and deep crack repair, and achieves efficient and long-term microbial self-repair effect.
Patent Information
- Application Number
- CN202411852043.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-29
AI Technical Summary
Existing microbial self-repair concrete has problems of reduced compatibility and inefficiency in high alkali environments and deep crack repair.
The carrier material is used to solid-load nitrate reducing bacteria and modified mesoporous silicon to form a three-dimensional network structure with fibers through microbial self-repairing agents, thereby improving the survival rate and repair efficiency of microorganisms in concrete.
It significantly improves the repair effect of deep cracks inside concrete, enhances tensile strength, extends self-repair benefits, and reduces the risk of environmental pollution.
Smart Images

Figure BDA0005190842540000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a green microbial self-repairing concrete. Background Art
[0002] Concrete has the characteristics of high compressive strength, easy molding and excellent durability. It is one of the most widely used building materials in the world. However, the early shrinkage of cement hydration and the low tensile strength and brittleness of concrete will cause it to be very easy to have micro cracks during normal service, which not only affects the beauty of the building, but also greatly reduces the service life of concrete. The amount of money spent on building maintenance each year is huge. Although traditional repair methods such as surface repair, grouting and filling methods can repair cracks to a certain extent, they are essentially passive repairs, time-consuming and labor-intensive, and have certain limitations. Therefore, it is of great significance to carry out effective crack repair, especially in the early stage of cracks, to prevent micro cracks from further developing into macro cracks and ensure the durability and safety of the structure.
[0003] Microbial self-repair technology is a technology that actively repairs concrete cracks. Its principle is: when concrete cracks occur, with the entry of air and moisture, the microorganisms in the crack area are activated, inducing calcium carbonate deposition, and then repairing the cracks and inhibiting further expansion of the cracks. The reason why microorganisms can produce carbonate precipitation is because of their mineralization, including controlled mineralization and induced mineralization. Controlled mineralization is mineralization caused by the activities of the organisms themselves, while induced mineralization is mineralization caused by changes in the surrounding environment caused by microorganisms. Carbonate mineralization deposition is affected by four factors: dissolved inorganic carbon concentration, Ca 2+ concentration, nucleation sites, and pH. Calcium carbonate precipitation requires sufficient Ca 2+ and carbonate ions; microorganisms provide nucleation sites for calcium carbonate deposition. Since the cell wall is negatively charged, calcium ions can be adsorbed on the cell wall surface and react with carbonate ions to produce calcium carbonate precipitation on the surface of microorganisms; and an alkaline environment is conducive to the occurrence of this process.
[0004] However, the high alkaline environment and dense structure inside concrete materials greatly reduce the compatibility of microorganisms with concrete materials, limiting the application and development of microbial self-repair. Based on the harsh environment inside concrete materials, using carrier materials to immobilize microorganisms can not only avoid direct contact between microorganisms and alkaline environments, but also provide a stable living environment for the growth and metabolism of microorganisms. Using carrier materials to immobilize microorganisms significantly improves the compatibility of microorganisms with concrete materials, providing a new idea for microbial self-repair of concrete cracks.
[0005] Patent (ZL201611096154.0) "Self-repairing regenerated concrete based on urease-producing microorganisms mineralization deposition and preparation method" discloses a self-repairing regenerated concrete based on urease-producing microorganisms mineralization deposition and its preparation method, which is composed of expanded perlite loaded with urease-producing microorganisms, cement, regenerated stone, sand, silica fume, water, urea, calcium chloride, urease-producing microorganism suspension and water reducer. It uses urease-producing microorganisms as concrete crack repair agents, produces urease through the metabolism of urease-producing microorganisms, and decomposes urea into NH 4+ and CO3 2- , and then mineralize and deposit calcium carbonate to repair cracks. However, the urease-producing microorganisms used in this method produce a large amount of ammonia when generating mineralized deposition products, which pollutes the environment and has a poor effect on repairing deep cracks inside concrete.
[0006] Patent (ZL201610385109.0) "Self-repairing concrete using aerobic alkaliphilic microorganisms and its preparation method" discloses a self-repairing concrete using aerobic alkaliphilic microorganisms and its preparation method, and its components are expanded perlite, cement, gravel, sand, silica fume, water, calcium lactate and water reducer loaded with aerobic alkaliphilic microorganism repair agents. The self-repairing concrete uses aerobic alkaliphilic microorganisms as crack repair agents. When cracks appear in the concrete, the entry of water and air restores the metabolic function of the dormant microorganisms and converts calcium lactate into calcium carbonate precipitation, thereby achieving the purpose of self-diagnosis and repair of concrete cracks. However, the aerobic alkaliphilic microorganisms used in this method require sufficient oxygen when generating mineralized deposition products, making it difficult to repair deep cracks inside concrete with low oxygen content, and the material transfer efficiency between high pores is low, which affects the efficiency of microbial mineralization deposition, thereby reducing the strength recovery rate of microbial self-repairing concrete.
[0007] Patent (ZL201910418684.X) "Three-dimensional self-repairing concrete with crack depth and width based on microorganisms and its preparation method" discloses a three-dimensional self-repairing concrete with crack depth and width based on microorganisms and its preparation method. Its components are microbial self-repairing agent, bacteria-loaded expanded perlite, oxygen slow-release agent, nutrient-loaded expanded perlite, 120-mesh expanded perlite, cement, gravel, sand, silica fume, polypropylene fiber, water reducer, and water. It forms a three-dimensional network structure with polypropylene fiber and microbial self-repairing concrete, providing sufficient nucleation sites for microorganisms to achieve better width and depth repair. However, this method is only applicable to the repair of concrete cracks in the early and middle stages. With the concentration of dissolved inorganic carbon in concrete and Ca in the later stage of hydration, the depth of the cracks will be improved. 2+ The reduction in concentration makes it difficult to maintain the long-term self-repair benefits of microorganisms. Summary of the invention
[0008] Based on the above research ideas, the purpose of the present invention is to provide a green microbial self-repairing concrete and a preparation method thereof, in order to increase the material transmission efficiency between the pores of the microbial self-repairing concrete, improve the repair effect of deep cracks inside the concrete, and maintain long-term self-repairing benefits.
[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0010] A green microbial self-repairing concrete, the components and weight parts are:
[0011] 400 parts of cement, 4-6 parts of modified mesoporous silica, 60-75 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400-1500 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0012] Preferably, the concentration of the nitrate-reducing bacteria suspension is 3.0 to 8.0×10 7 cells / mL, and the solvent was sterile distilled water.
[0013] Preferably, the content of each component of the microbial nutrient solution per liter is: 1L of distilled water, calcium nitrate (excluding NO 2- , chemically pure) 1g, potassium nitrate 1g, disodium hydrogen phosphate 2g, glucose 1g, agar 1g, peptone 20g; the preparation method is: adjust the pH value of the culture medium to pH=10 with sodium hydroxide solution, and sterilize at high temperature.
[0014] Preferably, the fine aggregate is river sand with a particle size of 0.08 to 2 mm and a fineness modulus of 2.71.
[0015] Preferably, the coarse aggregate is modified granite with a particle size of 5 to 20 mm and continuous grading; the modification method is: high-temperature burning of the granite surface to produce fine pores and granular substances, thereby increasing the roughness of the stone to provide immobilization sites for microorganisms and their culture solutions.
[0016] Furthermore, the microorganism and its culture solution are immobilized in the following manner:
[0017] Y1: After mixing the nitrate-reducing bacteria suspension with the microbial nutrient solution, shake culture for 24 hours and centrifuge at 4000 r / min for 20 minutes to obtain bacterial sludge;
[0018] Y2: Resuspend the bacterial sludge in sterilized distilled water and then dilute it to obtain a bacterial cell concentration of (1.0-1.4)×10 7 cells / mL of bacterial solution;
[0019] Y3: The bacterial solution is adsorbed onto the surface and internal pores of the modified granite particles by a vacuum impregnation method, and then the modified granite adsorbed with the microbial solution is dried at a temperature of 40±2° C. to obtain bacteria-loaded modified granite.
[0020] Furthermore, the modification method of the modified mesoporous silica is, in the following order: pore expansion modification, amino functionalization modification and mineralization precursor immobilization modification;
[0021] The mesoporous silica preparation and pore expansion modification methods and steps are as follows:
[0022] S1: Dissolve 2 g of hexadecyltrimethylammonium bromide (CTAB) in 400 g of a water / methanol mixed solution (water:methanol=4:6, w / w). After the CTAB is completely dissolved, add 1.14 ml of a 1 M NaOH solution. The pH value of the solution should be about 11.0.
[0023] S2: Place the solution on a magnetic stirrer and stir vigorously at room temperature (400r / min), then quickly inject 3ml of tetraethyl orthosilicate (TEOS) solution, seal and stir for 8h, then store the solution in a sealed bottle that can withstand high temperature and pressure, place it in an oven at 80℃ for 12h, and white precipitate can be seen, while the upper layer of the solution is relatively clear;
[0024] S3: After cooling to room temperature, the solution is centrifuged to obtain a white precipitate, and then washed five times with deionized water + anhydrous ethanol in a centrifuge (4000 rpm) to remove excess CTAB and methanol; the white precipitate obtained after this step is mesoporous silicon without enlarged pores and CTAB removed;
[0025] S4: The obtained white precipitate does not need to be dried. 20 ml of anhydrous ethanol is added and the precipitate is placed in an ultrasonic oscillator for 0.5 h of shaking and dispersion. Then the solution is mixed with 20 ml of a mixture of water + 1,3,5-trimethylbenzene (1:1), and placed in a hydrothermal synthesis reactor in an oven at 140°C for 4 days for pore expansion reaction. The capacity of the hydrothermal reactor should be between 30% and 70%. If the capacity is too small, anhydrous ethanol can be added to supplement it. After sufficient cooling, the obtained product is washed 5 times with anhydrous ethanol + water in a centrifuge (4000 rpm).
[0026] S5: The product obtained this time is placed in 100 ml of hydrochloric acid alcohol (concentrated hydrochloric acid: anhydrous alcohol = 2:20, v / w) and condensed and refluxed for 20 hours. After being fully washed with anhydrous alcohol for 5 times, the product is dried at 80°C. The obtained white powder is macroporous mesoporous silica (LPMSN).
[0027] Furthermore, the amino functionalization modification method and steps of LPMSN are as follows:
[0028] Take 300 mg of LPMSN, ultrasonically disperse it in 100 ml of anhydrous toluene solution for 30 minutes, stir it at 200 rpm and heat it to boiling point, and slowly add 2 ml of 3-aminopropyltriethoxysilane drop by drop; connect a condenser reflux tube and continue heating and stirring for 24 hours, then cool it, centrifuge it at 4000 mp, wash it with alcohol solution 5 times to remove unreacted products and toluene, and dry it in an 80°C oven for 4 hours to remove residual alcohol solution; the white powder finally obtained is amino-functionalized macroporous mesoporous silica (AFMSN).
[0029] Furthermore, the AFMSN mineralization precursor immobilization modification method and steps are as follows:
[0030] P1: Use TBS buffer to prepare 18mM CaCl2 solution and 8.4mM K2CO3 solution; use deionized water to prepare 10mg / ml polyacrylic acid aqueous solution for standby use;
[0031] P2: Add the polyacrylic acid solution to the CaCl2 solution to obtain an 18 mM CaCl2 solution with a polyacrylic acid concentration of 600 pg / mL, which is recorded as complex solution α;
[0032] P3: 200 mg of AFMSN powder was placed in 50 ml of complex solution α and ultrasonically vibrated for 24 h to promote the complex solution α to enter the pores of AFMSN. After centrifugation at 4000 rpm for 3 min, it was washed with deionized water 3 times to remove the complex solution α with weak binding force, and a white powder was obtained;
[0033] P4: The obtained white powder was placed in a -70°C refrigerator for freeze-drying for 1 hour, and then the sample was freeze-dried in a freeze dryer to obtain the final white powder, which is the modified mesoporous silica.
[0034] Preferably, the length of the modified stainless steel fiber is 9-16 mm, and the modification method is: using high-speed inert gas (500 m / s) to cold-spray and attach the freeze-dried modified mesoporous silica on the surface of the stainless steel fiber.
[0035] A method for preparing green microbial self-repairing concrete, the specific preparation method steps are as follows:
[0036] Z1. After slightly wetting the mixer, weigh the bacteria-loaded modified granite, sand and cement and pour them into the mixer for dry mixing for 2 minutes to ensure that the dry materials are evenly distributed to avoid stratification due to differences in density and particle size of the dry materials;
[0037] Z2. Slowly add the weighed water into the stirring pot, continue stirring for 2 minutes, then add a certain amount of water reducer, and control the stirring time to about 2 minutes. After stirring evenly, add the thickener to facilitate the uniform distribution of the fibers in the matrix;
[0038] Z3, slowly add the modified stainless steel fiber treated with cold spray modified mesoporous silica, and then continue stirring until the fiber is evenly distributed and then stop. The entire stirring time is controlled to be about 14 minutes;
[0039] Z4. After the mixing is completed, the mixture is poured into a mold and placed on a vibration table for sufficient vibration. After the film is sealed, it is placed at room temperature (20±2°C). After 24 hours, it is demolded and placed in a standard curing room (20±2°C, relative humidity of 95%). After curing for 28 days, the microbial self-repairing concrete is obtained.
[0040] Beneficial Effects
[0041] Compared with the related art, the green microbial self-repairing concrete of the present invention has the following beneficial effects:
[0042] (1) The use of porous carriers to load microorganisms, nutrients and mineral precursors avoids the negative impact of direct microbial addition on the survival of microorganisms, improves the survival rate of microorganisms inside concrete, reduces the negative effects of organic nutrients on concrete performance, and to a certain extent avoids the premature consumption of mineral precursors before concrete cracks occur.
[0043] (2) The ability of denitrifying bacteria to mineralize and produce calcium carbonate precipitation in an environment lacking nutrients can be used to reduce the cost of repairing concrete cracks. The NO2 produced by its dissimilatory reduction reaction - It can also inhibit the corrosion of steel bars. In addition, nitrate-reducing bacteria can repair deep cracks under anaerobic conditions and improve the repair effect of deep cracks inside concrete.
[0044] (3) The tensile strength of microbial self-repairing concrete is significantly improved after stainless steel fibers are added, which reduces the width of cracks and provides attachment sites for mineral precursors, improves the efficiency of material transfer between concrete pores, and accelerates the mineralization and deposition process of nitrate-reducing bacteria.
[0045] (4) Modified mesoporous silica can react with Ca(OH)2 in concrete to form hydrated calcium silicate, which significantly improves the interfacial bonding strength between fiber and concrete. At the same time, mesoporous silica can be used as a mineralization precursor solid carrier to increase the concentration of inorganic carbon dissolved in concrete and Ca 2+ concentration, promoting carbonate mineralization deposition and maintaining long-term self-repairing benefits. DETAILED DESCRIPTION
[0046] The specific embodiments of the present invention are further described in detail below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0047] Example 1
[0048] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 4 parts of modified mesoporous silica, 60 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0049] The modified mesoporous silica modification method comprises, in order of modification, pore expansion modification, amino functionalization modification and mineralization precursor immobilization modification.
[0050] The mesoporous silica preparation and pore expansion modification methods and steps are as follows:
[0051] S1: Dissolve 2 g of hexadecyltrimethylammonium bromide (CTAB) in 400 g of a water / methanol mixed solution (water:methanol=4:6, w / w). After the CTAB is completely dissolved, add 1.14 ml of a 1 M NaOH solution. The pH value of the solution should be about 11.0.
[0052] S2: Place the solution on a magnetic stirrer and stir vigorously at room temperature (400r / min), then quickly inject 3ml of tetraethyl orthosilicate (TEOS) solution, seal and stir for 8h, then store the solution in a sealed bottle that can withstand high temperature and pressure, place it in an oven at 80℃ for 12h, and white precipitate can be seen, while the upper layer of the solution is relatively clear;
[0053] S3: After cooling to room temperature, the solution is centrifuged to obtain a white precipitate, and then washed five times with deionized water + anhydrous ethanol in a centrifuge (4000 rpm) to remove excess CTAB and methanol. The white precipitate obtained after this step is mesoporous silicon without enlarged pores and CTAB removed;
[0054] S4: The obtained white precipitate does not need to be dried. Add 20 ml of anhydrous ethanol and put it into an ultrasonic oscillator for 0.5 h of shaking and dispersion. Then mix the solution with 20 ml of a mixture of water + 1,3,5-trimethylbenzene (1:1), put it into a hydrothermal synthesis reactor and place it in an oven at 140C for 4 days for pore expansion reaction. Note that the capacity of the hydrothermal reactor should be between 30% and 70%. If the capacity is too small, anhydrous ethanol can be added to supplement it. After sufficient cooling, the obtained product is washed 5 times with anhydrous ethanol + water in a centrifuge (4000rpm);
[0055] S5: The product obtained this time is placed in 100 ml of hydrochloric acid alcohol (concentrated hydrochloric acid: anhydrous alcohol = 2:20, v / w) and condensed and refluxed for 20 hours. After being fully washed with anhydrous alcohol for 5 times, the product is dried at 80°C. The obtained white powder is macroporous mesoporous silica (LPMSN).
[0056] The amino functional modification method and steps of LPMSN are as follows:
[0057] Take 300 mg of LPMSN, ultrasonically disperse it in 100 ml of anhydrous toluene solution for 30 minutes, stir it at 200 rpm and heat it to boiling point, and slowly add 2 ml of 3-aminopropyltriethoxysilane drop by drop. Connect the condenser reflux tube and continue to heat and stir for 24 hours, then cool it down, centrifuge it at 4000 mp, wash it with alcohol solution 5 times to remove unreacted products and toluene, and dry it in an 80C oven for 4 hours to remove the residual alcohol solution. The white powder obtained at last is amino-functionalized macroporous mesoporous silica (AFMSN).
[0058] The AFMSN mineralization precursor immobilization modification method and steps are as follows:
[0059] P1: Prepare 18mM CaCl2 solution and 8.4mM K2CO3 solution using TBS buffer. Prepare 10mg / ml polyacrylic acid aqueous solution with deionized water for later use;
[0060] P2: Add the polyacrylic acid solution to the CaCl2 solution to obtain an 18 mM CaCl2 solution with a polyacrylic acid concentration of 600 pg / mL, which is recorded as complex solution α;
[0061] P3: 200 mg of AFMSN powder was placed in 50 ml of complex solution α and ultrasonically vibrated for 24 h to promote the complex solution α to enter the pores of AFMSN. After centrifugation at 4000 rpm for 3 min, it was washed with deionized water 3 times to remove the complex solution α with weak binding force, and a white powder was obtained;
[0062] P4: The obtained white powder was placed in a -70°C refrigerator for freeze-drying for 1 hour, and then the sample was freeze-dried in a freeze dryer to obtain the final white powder, which is the modified mesoporous silica.
[0063] The length of the modified stainless steel fiber is 9-16 mm, and the modification method is: using high-speed inert gas (500 m / s) to cold-spray and attach the freeze-dried modified mesoporous silicon according to claim 2 on the surface of the stainless steel fiber.
[0064] The concentration of the nitrate-reducing bacteria suspension is 3.0 to 8.0 × 10 7 cells / mL, and the solvent of the bacterial suspension was sterile distilled water.
[0065] The microbial nutrient solution preparation method is as follows: the content of each component of the culture medium per liter is 1L of distilled water, calcium nitrate (excluding NO 2- , chemically pure) 1g, potassium nitrate 1g, disodium hydrogen phosphate 2g, glucose 1g, agar 1g and peptone 20g; adjust the pH value of the culture medium to pH = 10 with sodium hydroxide solution and sterilize at high temperature.
[0066] The fine aggregate is river sand with a particle size of 0.08 to 2 mm and a fineness modulus of 2.71. Its solidity and mud content meet the requirements of the specifications and it belongs to medium sand in Zone II.
[0067] The coarse aggregate is modified granite with a particle size of 5 to 20 mm and continuous grading. The modification method is: high-temperature burning of the granite surface to produce fine pores and granular substances, thereby increasing the roughness of the stone and providing a fixation site for microorganisms and their culture solution.
[0068] The immobilization methods of microorganisms and their culture solutions are as follows:
[0069] Y1: After mixing the nitrate-reducing bacteria suspension with the microbial nutrient solution, shake culture for 24 hours and centrifuge at 4000 r / min for 20 minutes to obtain bacterial sludge;
[0070] Y2: Resuspend the bacterial sludge in sterilized distilled water and then dilute it to obtain a bacterial cell concentration of (1.0-1.4)×10 7 cells / mL of bacterial solution;
[0071] Y3: The bacterial solution is adsorbed onto the surface and internal pores of the modified granite particles by a vacuum impregnation method, and then the modified granite adsorbed with the microbial solution is dried at a temperature of 40±2° C. to obtain bacteria-loaded modified granite.
[0072] One of the specific preparation methods of green microbial self-repairing concrete is as follows:
[0073] Z1. After slightly wetting the mixer, weigh the bacteria-loaded modified granite, sand and cement and pour them into the mixer for dry mixing for 2 minutes to ensure that the dry materials are evenly distributed to avoid stratification due to differences in density and particle size of the dry materials;
[0074] Z2. Slowly add the weighed water into the stirring pot, continue stirring for 2 minutes, then add a certain amount of water reducer, and control the stirring time to about 2 minutes. After stirring evenly, add the thickener to facilitate the uniform distribution of the fibers in the matrix;
[0075] Z3, slowly add the modified stainless steel fiber treated with cold spray modified mesoporous silica, and then continue stirring until the fiber is evenly distributed and then stop. The entire stirring time is controlled to be about 14 minutes;
[0076] Z4. After the mixing is completed, the mixture is poured into a mold and placed on a vibration table for sufficient vibration. After the film is sealed, it is placed at room temperature (20±2°C). After 24 hours, it is demolded and placed in a standard curing room (20±2°C, relative humidity of 95%). After curing for 28 days, the microbial self-repairing concrete is obtained.
[0077] Example 2
[0078] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 5 parts of modified mesoporous silica, 65 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1450 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0079] The green microbial self-repairing concrete raw material modification method and specific preparation method are the same as in Example 1.
[0080] Example 3
[0081] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 6 parts of modified mesoporous silica, 70 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1500 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0082] The green microbial self-repairing concrete raw material modification method and specific preparation method are the same as in Example 1.
[0083] Comparative Example 1
[0084] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 4 parts of modified mesoporous silica, 60 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0085] In this comparative example, except that the mesoporous silica was not subjected to pore expansion modification treatment, the remaining green microbial self-repairing concrete raw material modification methods and specific preparation methods were the same as those in Example 1.
[0086] Comparative Example 2
[0087] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 4 parts of modified mesoporous silica, 60 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0088] In this comparative example, except that the AFMSN mineralization precursor is not subjected to the solid loading modification treatment, the remaining green microbial self-repairing concrete raw material modification methods and specific preparation methods are the same as those in Example 1.
[0089] Comparative Example 3
[0090] A green microbial self-repairing concrete is prepared from the following components by weight: 400 parts of cement, 4 parts of modified mesoporous silica, 60 parts of stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
[0091] In this comparative example, the stainless steel fiber was not modified, and the modified mesoporous silica was only added to the concrete in the form of internal mixing. The remaining green microbial self-repairing concrete raw material modification methods and specific preparation methods were the same as in Example 1.
[0092] The mixed slurry in Examples 1 to 3 and Comparative Examples 1 to 3 was poured into a mold to prepare a test block, wherein the test block for compressive strength testing was a cubic test block of 100 mm × 100 mm × 100 mm in size. The crack repair test method was as follows: the microbial self-repairing concrete that had been cured for 3 days was pressed at a speed of 0.3 MPa / s using a WAW-1000KN microcomputer-controlled electro-hydraulic servo universal testing machine, and then the cracked concrete was repaired and cured, with a curing period of 28 days and 120 days. The crack repair situation was tested and recorded, and the compressive strength test was performed on the concrete after repair. The compressive strength test was performed in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". Among them, compressive strength recovery rate (%) = strength after repair / strength before cracking × 100%.
[0093] The specific results of the performance test are as follows:
[0094]
[0095] It can be seen from the table that the green microbial self-repairing concrete prepared in Examples 1 to 3 has excellent strength properties and self-repairing properties. The maximum crack repair width of the microbial self-repairing concrete at 28 days reaches 1.23 mm, and the highest average repair width reaches 0.86 mm. The long-term repair effect of the concrete can be maintained, and the 120d compressive strength repair rate can reach 66.2% to 69.2%, which can better meet the increasingly high requirements for the comprehensive performance of concrete in the construction field.
[0096] From the comparison between Comparative Example 1 and Example 1, it can be seen that after the pore expansion modification of mesoporous silica, the performance indicators of green microbial self-repairing concrete are improved, among which the maximum repair width and average repair width at 28 days are increased by 34.94% and 36.84%, respectively.
[0097] From the comparison between Comparative Example 2 and Example 1, it can be seen that after the AFMSN mineralized precursor is solid-loaded and modified, the self-repairing effect of concrete is significantly improved, the 28d compressive strength repair rate is increased by 22.1%, and the 120d compressive strength repair rate is increased by 27.6%, which helps to maintain long-term self-repair benefits.
[0098] From the comparison between Comparative Example 3 and Example 1, it can be seen that the respective repair indicators of concrete are significantly improved after the surface of stainless steel fiber is treated with cold sprayed modified mesoporous silica, indicating that providing suitable mineralization precursor attachment sites has a significant effect on improving the material transfer efficiency between concrete pores and the self-repair benefit.
[0099] The present invention is further described above with the aid of specific embodiments. Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various improvements are made using the method concept and technical solution of the present invention, or they are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A green microbial self-repairing concrete, characterized in that: The components and weight parts are: 400 parts of cement, 4-6 parts of modified mesoporous silica, 60-75 parts of modified stainless steel fiber, 30 parts of nitrate-reducing bacteria suspension, 20 parts of microbial nutrient solution, 700 parts of fine aggregate, 1400-1500 parts of coarse aggregate, 200 parts of water, 4 parts of water reducer, and 1 part of thickener.
2. The green microbial self-repairing concrete according to claim 1, characterized in that: The concentration of the nitrate-reducing bacteria suspension is 3.0 to 8.0×10 7 cells / mL, and the solvent was sterile distilled water.
3. The green microbial self-repairing concrete according to claim 1, characterized in that: The content of each component of the microbial nutrient solution per liter is: 1L of distilled water, calcium nitrate (excluding NO 2- , chemically pure) 1g, potassium nitrate 1g, disodium hydrogen phosphate 2g, glucose 1g, agar 1g, peptone 20g; The preparation method comprises the following steps: adjusting the pH value of the culture medium to pH=10 with a sodium hydroxide solution, and sterilizing the culture medium with high temperature.
4. The green microbial self-repairing concrete according to claim 1, characterized in that: The fine aggregate is river sand with a particle size of 0.08 to 2 mm and a fineness modulus of 2.
71.
5. The green microbial self-repairing concrete according to claim 1, characterized in that: The coarse aggregate is modified granite with a particle size of 5 to 20 mm and continuous grading; The modification method is: high temperature burning granite surface to produce fine pores and granular substances, thereby increasing the roughness of the stone to provide fixed sites for microorganisms and their culture fluid.
6. The green microbial self-repairing concrete according to claim 5, characterized in that: The microorganism and its culture solution are immobilized in the following manner: Y1: After mixing the nitrate-reducing bacteria suspension with the microbial nutrient solution, shake culture for 24 hours and centrifuge at 4000 r / min for 20 minutes to obtain bacterial sludge; Y2: Resuspend the bacterial sludge in sterilized distilled water and then dilute it to obtain a bacterial cell concentration of (1.0-1.4)×10 7 cells / mL of bacterial solution; Y3: The bacterial solution is adsorbed onto the surface and internal pores of the modified granite particles by a vacuum impregnation method, and then the modified granite adsorbed with the microbial solution is dried at a temperature of 40±2° C. to obtain bacteria-loaded modified granite.
7. A green microbial self-repairing concrete according to any one of claims 1 to 6, characterized in that: The modified mesoporous silica modification methods are as follows in the modification order: pore expansion modification, amino functionalization modification and mineralization precursor immobilization modification; The mesoporous silica preparation and pore expansion modification methods and steps are as follows: S1: Dissolve 2 g of hexadecyltrimethylammonium bromide (CTAB) in 400 g of a water / methanol mixed solution (water:methanol=4:6, w / w). After the CTAB is completely dissolved, add 1.14 ml of a 1 M NaOH solution. The pH value of the solution should be about 11.
0. S2: Place the solution on a magnetic stirrer and stir vigorously at room temperature (400r / min), then quickly inject 3ml of tetraethyl orthosilicate (TEOS) solution, seal and stir for 8h, then store the solution in a sealed bottle that can withstand high temperature and pressure, place it in an oven at 80℃ for 12h, and white precipitate can be seen, while the upper layer of the solution is relatively clear; S3: After cooling to room temperature, the solution is centrifuged to obtain a white precipitate, and then washed five times with deionized water + anhydrous ethanol in a centrifuge (4000 rpm) to remove excess CTAB and methanol; the white precipitate obtained after this step is mesoporous silicon without enlarged pores and CTAB removed; S4: The obtained white precipitate does not need to be dried. 20 ml of anhydrous ethanol is added and the precipitate is placed in an ultrasonic oscillator for 0.5 h of shaking and dispersion. Then the solution is mixed with 20 ml of a mixture of water + 1,3,5-trimethylbenzene (1:1), and placed in a hydrothermal synthesis reactor in an oven at 140°C for 4 days for pore expansion reaction. The capacity of the hydrothermal reactor should be between 30% and 70%. If the capacity is too small, anhydrous ethanol can be added to supplement it. After sufficient cooling, the obtained product is washed 5 times with anhydrous ethanol + water in a centrifuge (4000 rpm). S5: The product obtained this time is placed in 100 ml of hydrochloric acid alcohol (concentrated hydrochloric acid: anhydrous alcohol = 2:20, v / w) and condensed and refluxed for 20 hours. After being fully washed with anhydrous alcohol for 5 times, the product is dried at 80°C. The obtained white powder is macroporous mesoporous silica (LPMSN). The amino functionalization modification method and steps of LPMSN are as follows: Take 300 mg of LPMSN, ultrasonically disperse it in 100 ml of anhydrous toluene solution for 30 minutes, stir it at 200 rpm and heat it to boiling point, and slowly add 2 ml of 3-aminopropyltriethoxysilane drop by drop; connect a condenser reflux tube and continue heating and stirring for 24 hours, then cool it, centrifuge it at 4000 mp, wash it with alcohol solution 5 times to remove unreacted products and toluene, and dry it in an 80°C oven for 4 hours to remove residual alcohol solution; the white powder finally obtained is amino-functionalized macroporous mesoporous silica (AFMSN).
8. A green microbial self-repairing concrete according to any one of claim 7, characterized in that: The AFMSN mineralization precursor immobilization modification method and steps are as follows: P1: Use TBS buffer to prepare 18mM CaCl2 solution and 8.4mM K2CO3 solution; use deionized water to prepare 10mg / ml polyacrylic acid aqueous solution for standby use; P2: Add the polyacrylic acid solution to the CaCl2 solution to obtain an 18 mM CaCl2 solution with a polyacrylic acid concentration of 600 pg / mL, which is recorded as complex solution α; P3: 200 mg of AFMSN powder was placed in 50 ml of complex solution α and ultrasonically vibrated for 24 h to promote the complex solution α to enter the pores of AFMSN. After centrifugation at 4000 rpm for 3 min, it was washed with deionized water 3 times to remove the complex solution α with weak binding force, and a white powder was obtained; P4: The obtained white powder was placed in a -70°C refrigerator for freeze-drying for 1 hour, and then the sample was freeze-dried in a freeze dryer to obtain the final white powder, which is the modified mesoporous silica.
9. The green microbial self-repairing concrete according to claim 8, characterized in that: The length of the modified stainless steel fiber is 9-16 mm, and the modification method is: using high-speed inert gas (500 m / s) to cold-spray and attach the modified mesoporous silica that has been freeze-dried on the surface of the stainless steel fiber.
10. A method for preparing green microbial self-repairing concrete, characterized in that: The specific preparation steps are as follows: Z1. After slightly wetting the mixer, weigh the bacteria-loaded modified granite, sand and cement and pour them into the mixer for dry mixing for 2 minutes to ensure that the dry materials are evenly distributed to avoid stratification due to differences in density and particle size of the dry materials; Z2. Slowly add the weighed water into the stirring pot, continue stirring for 2 minutes, then add a certain amount of water reducer, and control the stirring time to about 2 minutes. After stirring evenly, add the thickener to facilitate the uniform distribution of the fibers in the matrix; Z3, slowly add the modified stainless steel fiber treated with cold spray modified mesoporous silica, and then continue stirring until the fiber is evenly distributed and then stop. The entire stirring time is controlled to be about 14 minutes; Z4. After the mixing is completed, the mixture is poured into a mold and placed on a vibration table for sufficient vibration. After the film is sealed, it is placed at room temperature (20±2°C). After 24 hours, it is demolded and placed in a standard curing room (20±2°C, relative humidity of 95%). After curing for 28 days, the microbial self-repairing concrete is obtained.
Citation Information
Patent Citations
Crack self-repairing concrete using aerobic basophilic microorganisms and preparation method thereof
CN106045400A
Self-healing recycled concrete for cracks based on urease-producing microbial mineralization deposition and its preparation method
CN106699026B
Microorganism-based crack depth-width three-dimensional self-repairing concrete and preparation method thereof
CN110105007A
Cited By
Lightweight self-repairing concrete and preparation method thereof
CN120398472A
Self-repairing concrete based on modified carbon fibers and preparation method thereof
CN121377653A